Multiple range study of factors controlling the transmission of an emerging zoonotic agent, Echinococcus multilocularis - Guislain, Marie-Hélène (CCSD, 2006)
Alveolar echinococcosis, which can be lethal if diagnosed too late, is an emerging disease. This zoonosis is caused by the cestode Echinococcus multilocularis, which sylvatic cycle implies the red fox Vulpes vulpes, as definitive host, and the common and water voles Microtus arvalis and Arvicola terrestris as intermediate hosts. Human can be contaminated by ingestion of parasite eggs laid on vegetables or via direct contact with definitive hosts. A few data are currently available on ecological factors modulating parasitic transmission between their different hosts on regional and local perception ranges. We conducted a study on E. multilocularis cycle pattern on different perception ranges, in the french departement of the Ardennes, considered as a new endemic area. The prevalence of E. multilocularis in fox population reached 53%, which might be explained by a relatively high fox population density and an important consumption of Microtus sp. by the red fox. On a regional range (900 km²) and with a local grain (1 km²), the prevalence in red fox as well as individual worm burden distribution was very heterogeneous, with a strong gradient increasing from north to south. The majority of the parasitic biomass was harboured by a few red foxes within some square kilometres. Landscape characteristics and intermediate host densities seemed to influence E. multilocularis prevalence in red foxes. Finally, on a local range (90 km²) and with a micro-local grain (1000 m²), parasitic transmission seemed to occur more likely in edges, where red fox faeces and rodent densities were high. L'échinococcose alvéolaire, qui peut être fatale si le diagnostic est tardif, est une zoonose émergente. Elle est due à un cestode, Echinococcus multilocularis, dont le cycle fait intervenir le renard roux, Vulpes vulpes, comme hôte définitif et les campagnols prairiaux (Microtus arvalis et Arvicola terrestris) comme hôtes intermédiaires. Relativement peu de données sont actuellement disponibles sur les facteurs écologiques qui peuvent ...